Study of Virtual Reality Immersive Technology Enhanced Mathematics Geometry Learning - Su, Yu-Sheng; Cheng, Hung-Wei; Lai, Chin-Feng (Frontiers in Psychology, 2022)
Mathematics is an important foundation for the development of science education. In the past, when the instructors taught mathematical concepts of geometry shapes, they mostly used traditional textbooks and aids to conduct teaching activities, which resulted in students may not be able to understand the principles exactly. Nowadays, it has become a trend to integrate emerging technologies into mathematics courses and to use digital instructional aids. Emerging technologies can effectively enhance students' sensory experience while strengthening their impressions and understanding of subject concepts. In this paper, we apply virtual reality immersive technologies to develop a virtual reality mathematics geometry teaching system, which is used to teach mathematical geometry concepts. Teachers use the system to develop three basic mathematical geometry learning materials as "Triangular pyramid volume = 1/3 prism volume", "Cone volume calculation", and "Triangle center of gravity derivation". In the experimental activity, the teacher uses virtual reality teaching aids to guide students to learn mathematical geometry concepts in a fun way so that they can achieve the effectiveness of immersive learning. This study explores the impact of using the virtual reality mathematics geometry teaching system on students’ technology acceptance, learning motivations, and learning performance. The experimental result showed that using the virtual reality mathematics geometry teaching system can improve the learning motivations and learning performance of students.